APPLICATION OF RULES OF INTERNATIONAL HUMANITARIAN LAW IN INTERNATIONAL PEACE AND SECURITY OPERATIONS - Piskun, Ivan; Dudnik, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to analyze published documents and materials on the application of international humanitarian law norms in international operations to maintain peace and security, to identify problems that arise during the application of international humanitarian law norms in the conduct of modern international operations to maintain peace and security. Research methods: the basis of the methodological base of the study was the method of analysis and synthesis, as well as the comparative method. Results: the scientific paper examines the problematic issues arising from the participation of peacekeeping personnel in international peace and security operations, in particular: the compatibility of international humanitarian law and international human rights law in international peace and security operations; humanitarian intervention and intervention of peacekeeping forces in the internal affairs of the state in order to protect the population. Discussion: in the process of studying of mentioned problems the problem of so-called conflict of laws arising in the process of application of both branches of international law was highlighted. Conflicts or contradictions arise when the norms of one of the above-mentioned branches of international law contradict the other in the process of occurrence of a specific situation. Conflicts in the context of applicable law are primarily about the relationship between life and health, will, honor and dignity, etc. During the analysis of mentioned issues it was found that the principles of Roman law, in particular «lex specialis», are used to avoid them, when the special law cancels (extracts) the general law in accordance with the specific situation.